PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN SUPERVISI AKADEMIK TERHADAP MUTU SEKOLAH DI SMP BATANG TIMUR KABUPATEN BATANG - Yulinda Sari; Muhdi; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the influence of transformational leadership style and academic supervision on school quality in junior high schools in Batang Timur, Batang Regency. Transformational leadership style includes dimensions such as idealized influence, inspirational motivation, intellectual stimulation, and individual attention. Academic supervision, carried out by the principal, plays an important role in improving the quality of education through systematic planning, implementation, and evaluation of teacher performance. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 252 teachers in junior high schools in Batang Timur. The results showed that transformational leadership style has a positive and significant influence on school quality with a regression coefficient value of 0.385, which means that every one-unit increase in transformational leadership will increase school quality by 0.385 units. Academic supervision has a stronger influence with a regression coefficient value of 0.504, which shows that every one-unit increase in academic supervision will increase school quality by 0.504 units. Overall, academic supervision has a more dominant influence than transformational leadership, with a difference of 0.119 units. This study shows that the combination of effective transformational leadership and quality academic supervision can have a greater impact on improving school quality. These results provide recommendations for school principals to further optimize the role of academic supervision and develop a transformational leadership style to improve the quality of education in junior high schools in Batang Timur and its surroundings.